Foreign Direct Investments and Mergers and Acquisitions in Slovakia - Soltés, Vincent; Pürstinger, Gerhard (Theory, Methodology, Practice – Review of Business and Management, 2007)
The paper gives answer why Slovakia is so attractive for Foreign Direct Investments. There are discussed economics factors in Slovakia and there are compared with economics factors in some another countries.